Analysis of Instagram Media Account @Sapawargasby Surabaya City Government About Covid-19 Information: Analisis Akun Media Instagram @Sapawargasby Pemerintah Kota Surabaya Tentang Informasi Covid-19 - Rohman, Habibur; Aesthetika, Nur Maghfirah (Universitas Muhammadiyah Sidoarjo, 2021)
The Surabaya city government through the Department of Communication and Information Technology currently uses Instagram social media with the name @sapawargasby as a medium for publishing information, especially regarding Covid-19 during this Pandemic. The type and basis of this research is descriptive qualitative. The results of the study show that the seven characteristics of @sapawargasby are able to describe and define Surabaya itself, the available features are also used properly for means of publication and providing information. The @sapawarga account has fulfilled all the points of media wealth and government communication principles, so this account deserves to be one of the latest sources of information for Surabaya residents.